QUESTION ANSWERING SYSTEM DAN PENERAPANNYA PADA ALKITAB - Gunawan Gunawan; Gita Lovina (Jurnal Informatika, 2006)
Question answering system is a system that allows user to state his or her information need in the form of natural language question, and return short text excerpts or even phrases as an answer. The availability of a wide and various information source and improvements in the techniques of natural language processing, information extraction (wrapper), and information retrieval give a big effect on the development of question answering system, from just answering questions in a specific domain by consulting to structured information source such as database, and like in this research, answering any questions based on information stored in an unstructured text collection. A general architecture of question answering system based on text consists of six processing stages, i.e. question analysis, document collection preprocessing, candidate document selection, candidate document analysis, answer extraction, and response generation. Application of question answering system like AnswerBus, Mulder, and Webclopedia that are developed with its own characteristics has similar processing steps as in the general architecture. Answers returned by a question answering system need to be evaluated for performance measure. This research completed with a simple question answering system application using english Bible in World English Bible (WEB) version as the source of information to answer some questions. Because specific domain is selected: Bible, questions that can be posed by user could ask about information in the Bible itself only. Question is also limited to three types of answers that can be supported by the application: person (who), location (where), and date (when). Abstract in Bahasa Indonesia : Question answering system (QA system) adalah sistem yang mengijinkan user menyatakan kebutuhan informasinya dalam bentuk natural language question (pertanyaan dalam bahasa alami), dan mengembalikan kutipan teks singkat atau bahkan frase sebagai jawaban. Ketersediaan sumber informasi yang luas dan bervariasi, serta adanya perkembangan yang pesat dari teknik Natural Language Processing (NLP), Information Extraction (IE), dan Information Retrieval (IR) sangat mempengaruhi perkembangan dari QA system, yang mana dulunya hanya dapat menjawab pertanyaan-pertanyaan yang terbatas pada suatu bidang (domain) tertentu dengan berdasarkan pada sumber informasi yang terstruktur seperti database, hingga kini dapat menjawab berbagai jenis pertanyaan dengan bersumber pada informasi dari sebuah koleksi teks yang tidak terstruktur. Umumnya arsitektur question answering system yang berbasis teks dibangun atas enam tahapan proses, yaitu analisis pertanyaan, preprocessing koleksi dokumen, pemilihan kandidat dokumen, analisis kandidat dokumen, ekstraksi jawaban, dan pemberian respon. Aplikasi-aplikasi QA system (baik yang dapat diakses melalui internet maupun tidak) yang dikembangkan dengan ciri khasnya masing-masing memiliki urutan proses yang tidak jauh berbeda satu dengan lainnya. Jawaban yang dikembalikan oleh sebuah QA system sebagai respon terhadap pertanyaan perlu dievaluasi untuk menilai performansi sistem. Tulisan ini dilengkapi dengan sebuah aplikasi QA system dengan menggunakan Alkitab berbahasa Inggris versi World English Bible (WEB) sebagai sumber informasi untuk menjawab pertanyaan. Pemilihan domain Alkitab menyebabkan sejumlah pertanyaan yang dapat diajukan terbatas pada informasi yang tersimpan dalam Alkitab itu sendiri. Selain itu pertanyaan juga dibatasi pada tiga buah tipe jawaban, yaitu Person, Location, dan Date. Kata kunci: question answering system, natural language processing, information retrieval, information extraction, named entity recognition, part of speech tagging.